Experiences of the transition from a Traditional to an Integrative Project-based Curriculum - Mitchell, John; Tilley, Emanuela (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
In 2012, the UCL Faculty of Engineering Sciences made a major revision of its undergraduate curricula, through the implementation of the Integrated Engineering Programme (IEP). The academic year, 2023/2024, saw the IEP celebrate 10 years of new student intake into the reformed degree programmes which aimed to enhance the skills and societal awareness of graduates through a series of project-based learning experiences, integrated with a curriculum of instruction. Over these 10 years, it has evolved - through conscious action to improve but sometimes through unintended consequences of institutional initiatives or local developments. This paper documents the reflections of two leading members of the development team and shares experiences of implementing and maintaining a major curriculum reform focused on a student- centred, active and experiential approach to learning and teaching in a large, research-intensive university. It leverages a survey of alumni to highlight achievements, challenges and perceptions of this approach as seen by both staff and students. It considers the relationship between pedagogical ideologies and the practicalities of change within existing structures and the challenges of legacy within the institution. It aims to provide insight and support to those leading and managing programme-wide curriculum change.